2021
DOI: 10.1039/d1ra03452a
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the direct DME synthesis from CO2 rich syngas under variation of the CZA-to-γ-Al2O3 ratio of a mixed catalyst bed

Abstract: Experimental and numerical kinetic investigations for the direct DME synthesis resulted in one of the predictive models with the broadest range of validity in the open literature for the CZA/γ-Al2O3 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Here, CO conversion (29.3 mol%) is increasing up to a CZA : γ-Al 2 O 3 weight ratio of 5, however, accompanied by a decrease in DME selectivity (7.9 mol%). In a recent study, Delgado Otalvaro et al 21 found similar results with a variable CO 2 /CO x feed, where an increasing CZA/γ-Al 2 O 3 ratio promotes CO x conversion and a DME yield at a low CO 2 content in the feed; however, a high CO 2 feed content significantly reduces DME selectivity.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Here, CO conversion (29.3 mol%) is increasing up to a CZA : γ-Al 2 O 3 weight ratio of 5, however, accompanied by a decrease in DME selectivity (7.9 mol%). In a recent study, Delgado Otalvaro et al 21 found similar results with a variable CO 2 /CO x feed, where an increasing CZA/γ-Al 2 O 3 ratio promotes CO x conversion and a DME yield at a low CO 2 content in the feed; however, a high CO 2 feed content significantly reduces DME selectivity.…”
Section: Introductionmentioning
confidence: 63%
“…In this context, it should be noted that changing the CO x source from CO to CO 2 increases water production (R3) typically leading to a rapid decrease in dehydration performance when γ-Al 2 O 3 is used. 19,21,27,29 In comparison, when the dehydration of MeOH takes place over a solid acid component with fewer Lewis acid sites (known to adsorb water) such as FER, 15,27 HZSM5 (ref. [45][46][47] or SAPO, 48 high DME productivity can be maintained even at an increased CO 2 content in syngas or in the presence of increased water content.…”
Section: Dme Productivity Vs Czz/fer Variationmentioning
confidence: 99%
“…Numerous investigations have been carried out to describe and simulate the influence of feeds with variable CO/CO 2 content and different catalyst bed compositions, based on the thermodynamics and kinetic data. Accordingly, models have been proposed to quantitatively describe the process of direct DME synthesis and to derive predictions 131, 157, 158. Model‐based optimization studies on the composition of the dual catalyst bed revealed that an optimized distribution with an increased amount of methanol catalyst enhances the catalytic performance, allowing a significant shift towards the equilibrium CO resp.…”
Section: Dme Synthesismentioning
confidence: 99%
“…CO 2 conversion [156,158,159]. Different modeling approaches have been used to model the direct DME synthesis, the coupling of methanol formation models [106,107,110] and its dehydration [160,161] is one of the first approaches used, however, in the last years, lumped kinetic models based on prior knowledge on the direct CO/CO 2 conversion to DME are being developed [157,158,162]. These simplified models suffer from difficulties associated to possible model shortcomings caused by assumptions and uncertainties of the mathematical description, especially outside the fitted operation conditions.…”
Section: Process Modeling Dmementioning
confidence: 99%
See 1 more Smart Citation